ANALISIS KINERJA MENGGUNAKAN BALANCED SCORECARD PADA PERUSAHAAN DAERAH AIR MINUM ( Studi Kasus pada PDAM Kabupaten Batang ) - Belva Selado, Ryan; Kiswara, Endang (Diponegoro Journal of Accounting, 2014)
In the face of a tight business competition right now, the company required performance measurement method that can evaluate the comprehensive performance of company . Performance measurement tool is Balance Scorecard, can be combinate financial and non financial measurement. Balance Scorecard measures performance from 4 perspective, that is financial perspective, customer perspective, internal business perspective and learning & growth perspective. This research was conducted using data in 2011 and 2012, a questionnaire on customer and employees of PDAM Kabupaten Batang. The population of this research is employees and customer of PDAM Kabupaten Batang, with sample taken each respondent was 30 to 300 from employees and customer. The questionnaire was tested for validity and reliability. Perspective used in this research is consists of the Financial Perspective with indicator of liquidity ratios, rentability ratios, and solvency ratios. Next, the Customer Perspective with the indicators the level of costumer satisfaction, market share, and the completion complain from customer. Then Internal Business Perspective with the indicators the level efficiency of production, the level of lost product, with the gauge calibration. And the last, is learning and growth perspective with the indicators the level of employee satisfaction, employee training, and the level of ratio employee to customer. From the results of research by using concept of Balance Scorecard, can be concluded that performance of PDAM Kabupaten Batang as whole as good. In the financial perspective with the indicators of liquidity ratios, rentability ratios, and solvency ratios showed a good performance. For the customer perspective shows good performance with a value 3,73. At the company internal business perspective showed a good innovation. And for growth and learning perspective suggest that the level of employee satisfaction with a value 3,79. Data from these research it can be concluded that by using Balance Scorecard, can provide performance evaluation of the PDAM Kabupaten Batang in order permanent stand and to better in the next period